Találkozások, inspirációk és a közös szolgálat. A KALOT református kapcsolatai - Éva PETRÁS (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2022)
Encounters, Inspirations, and Approaches to Social Service. The Relationship of the Catholic Youth Movement of Agricultural Workers (KALOT) with the Reformed Church. The Catholic Youth Movement of Agricultural Workers (KALOT) was estab-lished in 1935 owing to the initiatives of Jesuit father Jenő Kerkai. In a couple of years, it became the most successful Catholic corporative movement in Hungary with 500,000 members. KALOT was engaged in the Hungarian social question and struggled for an agrarian reform policy. During World War II, its members and leadership also took part in the illegal, anti-fascist resistance movement. In 1945, KALOT started its post-war reorganization, but among the new political circumstances, it fought for its survival in vain: in 1946, it was banned by the communist Ministry of the Interior. The study examines KALOT’s relationship with the exponents of the Re-formed Church and its movements. Based on archival research, a mutual cooper-ation between the denominational movements is proven, which also shows the first results of an ecumenical dialogue and practice.